ANALISIS KEBUTUHAN PELAYANAN SOSIAL KORBAN BENCANA ALAM - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2005)
(Need Assessment of Social Setvices for Disaster Victims) - Disaster is the natural event that could not be detacted from geoligical condition, topography and indonesian geograpical condition. As result, disaster is a kind of normal event, it is not strange. However, whenever the disaster comes, problem that have always been found such as weakness of coordination, evacuation obstacle , lateness of assistance and limitness of facility. Thus, social service management for the victim disaster has to be upgrade, so the focus and main objective of social could be optimally achieved.